Akibat Hukum atas Penyalahgunaan atau Tidak Dipertanggungjawabkannya Bantuan Keuangan Partai Politik - Diana Anggraeni Asyrofi; Sultoni Fikri (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2026)
This research examines The Legal Responsibility of Political Parties in the Use of Financial Assistance from the State Budget (APBN). Financial assistance to political parties represents a form of state support aimed at strengthening party institutions and enhancing their role in promoting political education among citizens. However, in practice, there are frequent occurrences of mismanagement and a lack of transparency in the use of such funds, which raises legal issues concerning accountability and the responsibility of political parties. This study employs a normative juridical research method with a statutory and conceptual approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials, analyzed qualitatively. The results of the study indicate that the legal responsibility of political parties in utilizing state financial assistance must be based on the principles of transparency, accountability, and compliance with applicable laws and regulations, particularly Government Regulation No. 1 of 2018 concerning Financial Assistance to Political Parties. Every political party is required to prepare a financial accountability report that must be audited by the Audit Board of Indonesia (BPK). In cases where violations such as fund misuse are found, administrative sanctions may be imposed, including the termination of financial assistance, and criminal sanctions may apply if elements of corruption are identified. Therefore, the legal accountability mechanism serves as an essential instrument to ensure clean, transparent, and integrity-based governance of political parties in accordance with the principles of good governance.